How Argentina became a super-exporter of agricultural and food products during the First Globalisation (1880–1929) - Pinilla, Vicente (2018)
The objective of this paper is to explain, from a cliometric perspective, the determinants of the growth of Argentina’s exports between 1880 and 1929. To do this, we have constructed a gravity model with the principal products exported each year by Argentina to its most important trading partners. In this way, we believe that this study constitutes a relevant and original contribution to the analysis of economic growth from a historical perspective and specifically in explaining the factors determining the export success of the settler countries during the first wave of globalisation. Our results show that Argentina’s export-led growth must be explained from both the supply and demand sides. We also find that the reduction in trade costs and trade liberalisation, especially the latter, boosted exports. We also support the idea that Argentina had a successful agro-export sector because it offered a diverse basket of products to the different European and American countries that consumed them. To sum up, we can conclude that Argentina took advantage of a multilateral and open economic system. Within this context, the country generally found a demand for its supply, which constitutes the key to explaining the magnitude and speed of Argentina’s export growth.